Changing patterns of marriage and cohabitation in post-reform China - Wang, W (2021)
Premarital cohabitation has gained increasing popularity in China in the post-reform era (after the economic reform started in 1978). The central theme of this thesis is to examine this phenomenon, in particular, the socio-economic characteristics of cohabitors, and how cohabitation is associated with assortative mating outcomes and marital dissolutions. Drawing data from China Family Panel Studies (2010-2016), this thesis investigates three types of associations in heterosexual marriages: (i) between cohabitation and educational attainment; (ii) between cohabitation and educational assortative mating, and (iii) between cohabitation and subsequent divorce. Moreover, gender differences in each association and how these associations change across marriage cohorts (early-reform, mid-reform, and late-reform) were examined in detail. Chapter 1 explores the association between educational attainment and premarital cohabitation among married individuals. The results show that the positive association between education and premarital cohabitation has not decreased but instead strengthened over time. This trend is more consistent for women than men. Chapter 2 examines the association between premarital cohabitation and educational assortative mating outcomes. The results show that the differences in homogamy patterns between married couples with and without cohabitation experience vary across educational levels. Moreover, marriages preceded by cohabitation are more likely to cross educational barriers. Chapter 3 examines the association between cohabitation and divorce. The significant positive effect of premarital cohabitation on the risk of divorce is only found among males, and this effect persists across marriage cohort. The results from this thesis indicate a significant difference between China and both Western countries and other East Asian countries. The findings suggest that China is developing different patterns and trends of demographic changes because of its unique institutional and cultural context.